P2RX7 in Dopaminergic Neurons of Ventral Periaqueductal Gray Mediates HTWP Acupuncture-Induced Consciousness in Traumatic Brain Injury - Tang, Huiling; Qin, Siru; Li, Wei; Chen, Xuyi; Ulloa, Luis; Zhu, Qiumei; Liu, Baohu; Gong, Yinan; Zhao, Yadan; Wang, Songtao; Li, Shanshan; Guo, Yongming; et al. (Frontiers in Cellular Neuroscience, 2021)
The induction of a coma by traumatic brain injury (TBI) is a crucial factor for poor clinical prognoses. We report that acupuncture at the hand twelve Jing-Well points (HTWP) improved consciousness and neurologic function in TBI rats. Gene chip analyses showed that HTWP acupuncture mostly activated genes modulating neuronal projections (P2rx7, P2rx3, Trpv1, Tacr1, and Cacna1d), protein secretion (Exoc1, Exoc3l1, Fgb, and Fgr) and dopamine (DA) receptor D3 (Drd3) in the ventral periaqueductal gray (vPAG), among which the expression rate of P2rx7 was the most obviously increased. Acupuncture also increased the expression and excitability of DA and P2RX7 neurons, and the DA neurons expressed P2RX7, P2RX3, and TRPV1 in the vPAG. Intracerebroventricular administration of P2RX7, P2RX3, or TRPV1 antagonists blocked acupuncture-induced consciousness, and the subsequent injection of a P2RX7 antagonist into the vPAG nucleus also inhibited this effect. Our findings provide evidence that acupuncture alleviates TBI-induced comas via DA neurons expressing P2RX7 in the vPAG, so as to reveal the cellular and molecular mechanisms of the improvement of TBI clinical outcomes by HTWP acupuncture.